2013
DOI: 10.1089/ars.2012.4768
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Peroxisomal Dysfunction and Impaired Pexophagy Promotes Oxidative Damage in Lipopolysaccharide-Induced Acute Kidney Injury

Abstract: Aims: We examined that (a) how the endotoxic stress affects peroxisomal function and autophagic degradation of peroxisomes-pexophagy, (b) how a superimposed dysfunction of lysosomes and pexophagy modifies responses to lipopolysaccharide (LPS), and (c) the mechanisms of peroxisomal contribution to renal injury. To accomplish this, we used lysosome-defective Lyst-mice in vivo and primary endothelial cells in vitro, and compared the responses with wild-type (WT) littermates. Results: LPS induced pexophagic degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 50 publications
3
31
0
Order By: Relevance
“…Our group demonstrated that systemic injection of a sublethal dose of endotoxin induces a biphasic response starting with a transient decrease followed by an increase of peroxisome numbers in the kidney of normal mice (102). Experimental studies revealed that peroxisomes have a half-life of 48 h and are mainly degraded by autophagy under basal conditions (44).…”
Section: Septic Akimentioning
confidence: 99%
See 1 more Smart Citation
“…Our group demonstrated that systemic injection of a sublethal dose of endotoxin induces a biphasic response starting with a transient decrease followed by an increase of peroxisome numbers in the kidney of normal mice (102). Experimental studies revealed that peroxisomes have a half-life of 48 h and are mainly degraded by autophagy under basal conditions (44).…”
Section: Septic Akimentioning
confidence: 99%
“…The loss of catalase activity during renal ischemia is largely caused by the inactivation of the enzyme. Ischemia-induced generation of H 2 O 2 , together with (102). To see this illustration in color, the reader is referred to the web version of this article at www.liebertpub.com/ars intracellular acidosis, predisposes catalase to form an enzymatically inactive complex.…”
Section: Ischemic Akimentioning
confidence: 99%
“…It is proposed that proinflammatory cytokines generated from glomeruli could spread inflammation along the tubules through peritubular capillaries (85). Heightened PRR activation in the endothelium is another important source of inflammation (86,87), while properly activated endothelium is critical for mobilizing immune cells and clearing microbes (88). We also point out that because of the sentinel nature of innate immunity, studies have primarily focused on acute pathologic changes rather than long-term consequences of PRR activation, such as its role in fibrosis (89)(90)(91).…”
Section: How the Innate Immune System Senses Trouble And Causes Troubmentioning
confidence: 99%
“…A physiological association has been made between disease states and altered peroxisome turnover in primary endothelial cells, wherein impaired peroxisome homeostasis and function result from induced renal toxicity or sepsis (33). Artificial induction of pexophagy has been reported in mammalian cells by fusing ubiquitin moieties to PEX3 and PMP34 (34).…”
mentioning
confidence: 99%